The Integrity of Bio-Stimulant Efficiency of Mint Leaf (Mentha Piperita) on Crude Oil Remediation in Soil Environment - Vector Chukwuemeka Ukpaka; Joy Chukwuemeka Peter Ukpaka; Abraham Peter Ukpaka; Ukpaka Chukwuemeka. Peter (International Journal of Pollution: Prevention & Control, 2026)
This research addresses the integrity of biostimulant efficiency of mint leaf (Mentha piperita) on crude oil remediation in soil environments. The soil environment consideration in this investigation is loamy and some soil properties were examined; obtained data revealed a nitrogen value of 5.82%, phosphorus value of 46.91mg/kg, potassium value of 417.51mg/kg, and hydrogen-utilizing bacteria (HUB) value of 13.19cfu/g for unpolluted loamy soil, whereas polluted soil with crude oil data are 1.02% nitrogen, 1.326mg/kg phosphorus, 42.18mg/kg potassium, and 81.6cfu/g HUB. The properties of the biostimulant used revealed a nitrogen concentration of 6.93%, phosphorus of 52.271mg/kg, potassium of 463.902mg/kg, and HUB of 10.21cfu/g for sun-dried mint leaf samples, whereas room-dried nitrogen value is 9.47%, phosphorus value is 74.113mg/kg, potassium value is 552.542mg/kg, and HUB value is 13.98cfu/g. The density and kinematic viscosity of the crude oil used are 0.861g/ml and 2.84mm²/s. Crude oil remediation was monitored for a period of 35 days and the percentage reduction in the total petroleum hydrocarbon concentration determined. Application of sun-dried biostimulant revealed TPH reduction values in terms of percentage removal within the range of 1.43% to 77.88% for intervals of 7 to 35 days with a 50g dosage of remediant and 4.51% to 91.14% for 100g dosage, whereas room-dried biostimulant application demonstrates 2.38% to 78.53% for 7 to 35 days of 50g dosage and 8.41% to 92.29% for 100g dosage of remediant. In the control sample, obtained data revealed 1.13% to 25.67% for the period of 7 to 35 days. This research revealed that mint leaf (Mentha piperita) characteristics possess the integrity of good biostimulant efficiency for use in treating soil contaminated with crude oil. However, the room-dried sample is higher in efficiency than sun-dried, comparing percentage reduction of TPH concentration from 2.38% to 78.53% for intervals of 7 to 35 days of 50g dosage against 1.43% to 77.83% for the sun-dried value. This investigation has demonstrated the significance of the biostimulant in crude oil remediation.
Keywords: biostimulant; crude oil; efficiency; integrity; mint leaf; remediation; soil